Studi Morfologi Domba Ekor Gemuk Silangan (DEGS) Di Lembah Palu - Irfan, Mohamad; Dg. Malewa, Amiruddin (FAPETKAN UNTAD, 2012)
This Research target to know the comparison form and size measure of parts of body (morfologi) of Fat Tail Sheep Livestock Traverse (female and Masculine DEGS) residing in Countryside of Bora and Chief Of Village Taipa Sulawesi Province. Parameter of livestock body qualitative and quantitative which Method used in this research is combination between